Tanah Hantu (Absentee) Sebagai Simtom Transformasi Sosial Ekonomi Masyarakat Pedesaan Lombok Timur - Humaedi, M. Alie; Pasisir, Aliena Anaqu Arung (Retorik: Jurnal Ilmu Humaniora, 2025)
The reality and practice of rural Indonesian society are always interesting to study, especially with respect to the issue of land ownership and livelihood systems related to the agricultural world. The second aspect seems to be related to their worldview, according to which land is proof of wealth that must be guarded until death or passed on to their children and grandchildren. However, with the increase in the necessities of life in the modern era, that view began to change. Land has now become an asset that can be bought and sold, and an investment that is full of interests in reorganizing space for the purposes of modern capitalism. Ghost (absentee) lands with unclear ownership or across regional boundaries are present amidst poverty. Conflicts of ownership and resolution of spatial reorganization are a continuation of the process of “ghost land transactions.” This paper attempts to reveal the existence of ghost land and its influence on the socio-economic transformation of rural communities in East Lombok, West Nusa Tenggara. Using qualitative ethnographic methods, including in-depth interviews with twenty informants and direct observation of related aspects, it was found that the phenomenon of ghost land is an inseparable part of community life. Ghost lands are caused by cross-regional sales, nominee purchases, and hidden interests in the reorganization of modern non-agricultural space. Emically, the existence of ghost land is a symptom (marker) of poverty in a society that is trying to adjust to the greed and interests of modern capitalism.